Principles Of Caution By Land Deed Officials In Preparing A Decd Of Sale And Purchase Of Land Ownership Rights - Arya Sayoga; Anak Agung Ayu Intan Puspadewi (Universitas Pendidikan Nasional, 2024)
ABSTRACT: The purpose of this research is to determine the principle of caution for land Decd officials in makeng Decds of sale and purchace of land ownership rights. The research method used in writing this thesis is using normative legal research methods and it can be concluded that: 1) The authority of a LDO to make authentic Decds regarding all legal acts of transition and imposition of rights concerning land and ownership rights. to apartment units located within work area. LDO in makeng authentic Decds is obliged to use the precautionary principle based on regulations relating to LDO and land rights. 2) The legal consequences of the LDO Decd if you do not use the precautionary principle in the process of binding the sale and purchace of land as an embodiment of legal certainty is that the LDO Decd can be canceled and null and void by law because it is not in accordance with article 22 of GR No.37 th.1998 that the LDO Decd must be read aloud. or the contents are explained to the parties in the presence of at least two witnesses to the Decd. KEYWORDS: LDO authority, precautionary principle, AJB